Developing a framework for social technologies in learning via design-based research - Parmaxi, Antigoni; Zaphiris, Panayiotis (My University, 2015)
Abstract This paper reports on the use of design-based research (DBR) for the development of a framework that grounds the use of social technologies in learning. The paper focuses on three studies which step on the learning theory of constructionism. Constructionism assumes that knowledge is better gained when students find this knowledge for themselves when engaging in the making of concrete and public artifacts. In an attempt to implement theoretically designed learning environments in real-world classrooms, DBR was employed as an overarching framework of inquiry. The three cycles of DBR inquiry provide deep insights into the use of social technologies as social constructionist tools and inform a novel framework for their use. The implementation of the framework is specified along with further implications for researchers and practitioners.
Keywords: social media; Social technologies; Web 2.0; Constructionism; Social constructionism; Computer-assisted language learning